2018
DOI: 10.1016/j.jacep.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Apixaban Dosing During Atrial Fibrillation Ablation

Abstract: Both uninterrupted and minimally interrupted apixaban at the time of AF ablation were associated with a very low rate of thromboembolic events, and rates of both major (<2%) and clinically significant bleeding were similar to uninterrupted warfarin. (Apixaban Evaluation of Interrupted Or Uninterrupted Anticoagulation for Ablation of Atrial Fibrillation [AEIOU]; NCT02608099).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 25 publications
2
58
1
1
Order By: Relevance
“…A total of 2694 records were identified, of which 29 studies met the predefined criteria and hence were included in the analysis. The detailed search flowchart was illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2694 records were identified, of which 29 studies met the predefined criteria and hence were included in the analysis. The detailed search flowchart was illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Of note, in that meta‐analysis, the efficacy and safety of interrupted NOACs vs interrupted VKAs were not specifically assessed. Furthermore, several studies have been published recently, among which the AEIOU study published online is a randomized cohort trial . Therefore, we comprehensively collected the published studies comparing NOACs and VKAs to evaluate the safety and efficacy of NOACs in AF patients undergoing catheter ablation and to investigate the differences in uninterrupted NOACs vs uninterrupted VKAs or interrupted NOACs vs interrupted VKAs.…”
Section: Introductionmentioning
confidence: 99%
“…Another question is whether every NOAC is effective in preventing periprocedural thromboembolic complications. RCTs with dabigatran (RE-CIRCUIT) and rivaroxaban (VENTURE-AF) did not show any thromboembolic events [5,6], while RCTs with apixaban (AXAFA, AEIOU) showed a low thromboembolic event rate [12,21].…”
Section: Discussionmentioning
confidence: 98%
“…The ABlation peRIoperative DabiGatran in use Envisioning in Japan (ABRIDGE-J) randomized trial demonstrated that anticoagulation with minimally interrupted dabigatran (1 or 2 doses withheld) was associated with fewer ISTH major bleeding complications than uninterrupted VKA with no increase in thromboembolic events (Table 3) [13]. In addition, the Apixaban Evaluation of Interrupted Or Uninterrupted anticoagulation for ablation of atrial fibrillation (AEIOU) randomized trial showed no difference between continuous apixaban compared with minimally interrupted apixaban (1 dose withheld) with regard to major bleeding (BARC 3-5) or thromboembolic events (Table 3) [21]. Finally, a recent meta-analysis of 4 randomized and 9 prospective observational studies (N = 5463) found that minimally interrupted and continuous NOAC strategy were both safe and non-inferior strategies compared with uninterrupted VKA [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation